Funkcija gospodarja volkov v povedkah, zagovorih, verovanjih in šegah - Mencej, Mirjam (Etnolog. Nova vrsta (Ljubljana), 2000)
The author compares the function of the "shepherd of the wolves", a mythical figure found in Slavic as well as non-Slavic folktales and beliefs as a person to whom people turn to in incantations, blessings, and prayers, seeking protection for their livestock and themselves. She also compares the function of various customs, intended for the protection against wolves.
Keywords: ethnology; etnologija; folkloristics; folkloristika; mitologija; mythology; verovanje; volkovi; povedke; zagovori; šege